Creation of individual few-layer graphene incorporated in an aluminum matrix. (September 2018) - Zhou, Weiwei; Fan, Yuchi; Feng, Xiaopeng; Kikuchi, Keiko; Nomura, Naoyuki; Kawasaki, Akira
Abstract: 3D-networks of few-layer graphene (FLG) platelets at grain boundaries, sandwiched between thin amorphous Al2O3 layers, were fabricated by spark plasma sintering (SPS) of graphene oxide (GO)/Al mixed powders. The GO was prepared by a modified Hummers' method, and was thermally reduced to FLG simultaneously during SPS densification. Subsequent plastic flow of the Al matrix during the hot extrusion process caused the destruction of this structure, rearranged the FLG platelets individually into the uniaxial direction, and made them incorporate in the Al matrix. Observations by high-resolution transmission electron microscopy proved the existence of a direct-contact interface between the FLG and the Al matrix without any interfacial compounds, and revealed that the Al matrix featured a fairly low dislocation density. Consequently, the mechanical strength of Al matrix was noticeably enhanced by FLG incorporation, agreeing with the potential strengthening effect predicted by the load transfer mechanism.